Is there an association between previous infection with Neisseria gonorrhoeae and gonococcal AMR? A cross-sectional analysis of national and sentinel surveillance data in England, 2015–2019. (4th March 2022) - Allen, Hester; Merrick, Rachel; Ivanov, Zdravko; Pitt, Rachel; Mohammed, Hamish; Sinka, Katy; Hughes, Gwenda; Fifer, Helen; Cole, Michelle Jayne
Abstract : Objectives: Quarterly STI screening is recommended for high-risk gay, bisexual and other men who have sex with men (MSM) in the UK, but frequent antibiotic exposure could potentially increase the risk of antimicrobial resistance (AMR) developing in Neisseria gonorrhoeae . We investigated whether repeat diagnosis of gonorrhoea in those attending sexual health services (SHS) was associated with reduced antimicrobial susceptibility. Methods: Antimicrobial susceptibility data relating to the most recent gonorrhoea diagnosis for each individual included in the Gonococcal Resistance to Antimicrobials Surveillance Programme (2015–2019) were matched to their historical records in the national GUMCAD STI surveillance data set (2012–2019). The number of gonorrhoea diagnoses in the previous 3 years was calculated for each SHS attendee. Logistic regression was used to examine the associations between the number of diagnoses and reduced susceptibility to ceftriaxone (minimum inhibitory concentration (MIC) >0.03 mg/L), cefixime (MIC >0.06 mg/L) and azithromycin (MIC >0.25 mg/L) at the time of the latest diagnosis. Results: Of 6161 individuals included in the analysis, 3913 (63.5%) were MSM, 1220 (19.8%) were heterosexual men and 814 (13.2%) were women. Among MSM, 2476 (63.3%) had 1 past gonorrhoea diagnosis, 1295 (33.1%) had 2–4, 140 (3.6%) 5–9, and 2 (0.1%) ≥10. Most women and heterosexual men (91.7%) had one past gonorrhoea diagnosis; none had more than four. Reduced ceftriaxone and cefixime susceptibility was more common among MSM with two to four gonorrhoea diagnoses (3.8% and 5.8%, respectively) compared with those with one (2.2% and 3.9%, respectively). After adjusting for potential confounding, this association remained (adjusted OR: 1.59, 95% CI 1.07 to 2.37, p=0.02; adjusted OR: 1.54, 95% CI 1.11 to 2.14, p=0.01). No evidence was found for any other associations. Conclusions: Among MSM, repeat diagnosis of gonorrhoea may be associated with reduced ceftriaxone and cefixime susceptibility. As these are last-line therapies for gonorrhoea, further research is needed to assess the impact of intensive STI screening on AMR.